Pengembangan Multimedia Interaktif Berbasis Flash pada Pembelajaran Tematik Kelas IV SDS Muhammadiyah Pasir Jaya Kabupaten Tangerang - Namiroh, Siti Yoyoh; magdalena, ina; Sa’odah, Sa’odah (Trapsila: Jurnal Pendidikan Dasar, 2020)
This study aims to produce flash-based interactive multimedia products that are suitable for thematic subjects with theme 3 sub-themes 1 learning 1 grade IV students of SDS Muhammadiyah Pasir Jaya, Tangerang Regency. This research is a type of research and development (Research and Development) using the Dick & Carey model. Data collection was carried out by observation, questionnaires. The data analysis technique uses qualitative and quantitative techniques. From the results of the validation data from media, multimedia and material experts (Thematic, Indonesian and Natural Sciences) the results of the validation show that the above average score is categorized as agree because it is included in the mean> 3.4 to 4.2, it can be concluded that the new policy on lecturer performance appraisal can be approved respondents to be implemented.